2017
DOI: 10.2967/jnumed.117.197350
|View full text |Cite
|
Sign up to set email alerts
|

A PET/CT-Based Strategy Is a Stronger Predictor of Survival Than a Standard Imaging Strategy in Patients with Head and Neck Squamous Cell Carcinoma

Abstract: Our purpose was to examine whether staging of head and neck squamous cell carcinoma (HNSCC) by upfront F-FDG PET/CT (i.e., on the day of biopsy and before the biopsy) discriminates survival better than the traditional imaging strategies based on chest x-ray plus head and neck MRI (CXR/MRI) or chest CT plus head and neck MRI (CCT/MRI). We performed a masked prospective cohort study based on paired data. Consecutive patients with histologically verified primary HNSCC were recruited from Odense University Hospita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…In a prospective cohort study from 2017, Rohde et al [43] concluded that PET/CT has a significantly higher detection rate of distant metastases or synchronous cancers than chest CT/head and neck MRI for patients with oral cavity cancer (T1-T4). The detection of distant metastasis and synchronous cancers at the time of diagnosis has a significant impact on treatment decisions and prognosis [20,44]. This qualifies more for a valid argument in favor of up-front PET/CT than of an improved sensitivity in detecting cervical lymph node metastases, as PET/CT has the significant impact of M-classification, thus affecting treatment planning for patients with OSCC.…”
Section: Perspectivesmentioning
confidence: 99%
“…In a prospective cohort study from 2017, Rohde et al [43] concluded that PET/CT has a significantly higher detection rate of distant metastases or synchronous cancers than chest CT/head and neck MRI for patients with oral cavity cancer (T1-T4). The detection of distant metastasis and synchronous cancers at the time of diagnosis has a significant impact on treatment decisions and prognosis [20,44]. This qualifies more for a valid argument in favor of up-front PET/CT than of an improved sensitivity in detecting cervical lymph node metastases, as PET/CT has the significant impact of M-classification, thus affecting treatment planning for patients with OSCC.…”
Section: Perspectivesmentioning
confidence: 99%
“…We conducted a masked prospective cohort study based on paired data. The overall cohort has previously been used for publications concerning patients with primary HNSCC (22)(23)(24). This study examined recurrent HNSCC, which constituted a different subgroup of patients from our overall cohort.…”
Section: Setting and Participantsmentioning
confidence: 99%